Fuzzy-PID hybrid controller for Point-to-point (PTP) positioning system - Muhammad , Mahbubur Rashid; Wali, Ahmad (EuroJournals Publishing, Inc., 2010)
Motion control systems play an important role in industrial engineering applications such as advanced manufacturing systems, semiconductor manufacturing system and robot systems. Until know, Proportional-Integral-Derivative (PID) controllers are still the most popular controller used in industrial control systems including motion control systems due to their simplicity and also satisfactory performances. The use of PID controller for motion control systems was proposed by many researchers. However, since the PID controller is developed based on the linear control theory, the controller gives inconsistent performance for different condition. In order to overcome this problem, Fuzzy-tuned PID control is proposed. By using fuzzy system in real-time, the PID controller can learn, adapt and change its parameters based on the condition of the controlled-object. The effectiveness of the proposed method is evaluated experimentally in real time using an experimental rotary positioning system. It is confirmed that the proposed system is better than classical PID controller in terms of not only positioning performance but also robustness to inertia variations.